Dampak Konflik Laut Cina Selatan Terhadap Hubungan Perdagangan Cina dan Korea Selatan - Suraya, Suraya (Journal of International and Local Studies, 2019)
In the research of this thesis, the authors conducted a study aimed at determining the relationship between the South China Sea conflict and trade relations between South Korea and China. The types of studies used are descriptive qualitative as well as quantitative. This type of writing is used to provide a clear picture of what is happening in the South China Sea that could affect international trade. While the data collection technique used was literature study, by searching for data relevant to the case study through national and international journals, statistical data, online news, and internet sources. The data obtained are primary data. Data analysis techniques used are qualitative and quantitative analysis techniques. The results of the study obtained by the authors, that is, there are two effects of the South China Sea conflict on trade relations between South Korea and China. First, trade instability in the South China Sea resulting in a decline in trade figures due to escalating conflict. Second, China's dominance in the South China Sea, which as a major player plays an important role, especially controlling the South China Sea and putting pressure on other countries. It often acts as a trigger for conflict even as China benefits from the South China Sea conflict. For South Korea-China trade relations that are more disadvantaged by South Korea, although an indirect influence, there are other dynamics that affect the relationship between the two such as THAAD